2017
DOI: 10.1007/s00011-017-1071-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sevoflurane on NF-кB and TNF-α expression in renal ischemia–reperfusion diabetic rats

Abstract: Sevoflurane exerted a protective effect against renal injury by lowering the expression of NF-кB and TNF-α in renal I/R diabetic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…This was usually accompanied by the release of inflammatory cytokines, such as TNF-α, IL-1β and IL-6. Studies 4 , 24 showed that the inflammatory response induced by I/R injury was further exacerbated in diabetic rats, in which TNF-a and IL-1β levels in serum or renal tissues increased significantly. In this study, we have demonstrated that administration of resveratrol proved to be effective to inhibit the expression of the pro-inflammatory cytokines TNF-α and IL-1β elevated in the kidney of diabetic rats after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…This was usually accompanied by the release of inflammatory cytokines, such as TNF-α, IL-1β and IL-6. Studies 4 , 24 showed that the inflammatory response induced by I/R injury was further exacerbated in diabetic rats, in which TNF-a and IL-1β levels in serum or renal tissues increased significantly. In this study, we have demonstrated that administration of resveratrol proved to be effective to inhibit the expression of the pro-inflammatory cytokines TNF-α and IL-1β elevated in the kidney of diabetic rats after I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the accumulation of ROS plays a significant role in I/R-induced kidney injury in diabetic patients (34). a previous study reported increased levels of BUN, serum creatinine and proinflammatory cytokines in diabetic rats that had experienced i/r injury (6). in the present study, it was observed that diabetes aggravated renal i/r injury through acute tubular damage and exacerbated kidney dysfunction; these effects were reflected by the higher levels of Bun and serum creatinine.…”
Section: Discussionmentioning
confidence: 97%
“…evidence has accumulated supporting the fact that dM aggravates renal i/r injury (5). experimental studies have revealed that diabetic rats develop renal dysfunction faster following ir injury compared with non-diabetic rats (6,7). other research has revealed that progressive hyperglycemia can cause increased levels of reactive oxygen species (roS) in the diabetic kidney following i/r injury (8).…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response is another important part of the pathophysiology implicated in kidney I/R injury [38] . Some proinflammatory cytokines such as IL-2, IL-6, TNF-α and IL-1β are released during kidney I/R injury [39,40] .…”
Section: Discussionmentioning
confidence: 99%